2018
DOI: 10.1111/resp.13407
|View full text |Cite
|
Sign up to set email alerts
|

Emerging therapies in adult and paediatric bronchiectasis

Abstract: Bronchiectasis is a chronic respiratory disorder characterized by persistent productive cough and recurrent chest infections secondary to permanent structural airway damage. The current treatment strategies for this debilitating disorder are limited to prompt antibiotic treatment of infective exacerbations and regular airway clearance techniques. Despite its high morbidity and associated mortality across all age groups, it has been a neglected area of research in respiratory medicine and there remain no licens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 99 publications
(179 reference statements)
0
7
0
Order By: Relevance
“…Downregulating ENaC has been suggested as a potential therapeutic strategy in both CF and PCD to reduce mucus viscosity and improve airway clearance. [43][44][45] The role of CFTR and CFTR mutations in bronchiectasis remains under debate in the literature, with conflicting studies being published. A study of 100 patients with idiopathic bronchiectasis in an Australian cohort found that the rate of classical CFTR mutations was 1:25, the same frequency as found in the general population.…”
Section: Mucociliary Functionmentioning
confidence: 99%
“…Downregulating ENaC has been suggested as a potential therapeutic strategy in both CF and PCD to reduce mucus viscosity and improve airway clearance. [43][44][45] The role of CFTR and CFTR mutations in bronchiectasis remains under debate in the literature, with conflicting studies being published. A study of 100 patients with idiopathic bronchiectasis in an Australian cohort found that the rate of classical CFTR mutations was 1:25, the same frequency as found in the general population.…”
Section: Mucociliary Functionmentioning
confidence: 99%
“…As previous studies on muscle training used different programmes, this promising intervention should be further evaluated in a larger study. Other emerging therapies in managing bronchiectasis, summarized in a recent review, include neutrophil elastase inhibitors, CXC chemokine receptor‐2 antagonists, dipeptidyl peptidase‐1 inhibitors, phosphodiesterase‐4 inhibitors, statins, epithelial sodium channel inhibitors and inhaled bacteriophages (as an alternative antimicrobial strategy), as depicted in Figure . To date, none are available.…”
Section: Other Treatment Options and Guidelinesmentioning
confidence: 99%
“…non‐antibiotic macrolides) and neutrophilic killing (e.g. tamoxifen and protease‐activated receptor‐1 antagonist) may play a future role (Reproduced from Regan and Hill, with permission).…”
Section: Other Treatment Options and Guidelinesmentioning
confidence: 99%
“…While the current approach of therapy is effective, the concern over the long-term use of inhaled antibiotics is that it will lead to the rise of antibiotic-resistant bacterial pathogens, resulting in worsened exacerbation of the disease [7,8]. For this reason, alternative treatment approaches that can break the vicious cycle of airways infection and inflammation have been actively investigated to complement antibiotic therapy [9].…”
Section: Introductionmentioning
confidence: 99%